Convergence of two-step inertial Tseng’s extragradient methods for quasimonotone variational inequality problems - Dung, Vu Tien; Anh, Pham Ky; Thong, Duong Viet (Communications in nonlinear science & numerical simulation, 2024)
This paper introduces two-step inertial Tseng’s extragradient methods with self-adaptive step sizes for solving quasimonotone variational inequalities in real Hilbert spaces. Under suitable conditions on the iterative parameters, weak convergence of the sequence generated by the proposed algorithms is obtained. Numerical results demonstrate the efficiency of the methods compared to others available ones in literature.